(untitled) (Research, Society and Development, 2021)
This study aims to describe the role of nurses in identifying factors associated with non-adherence to the elderly in the treatment of systemic arterial hypertension. Methodology is an integrative review. To select the studies, four databases were used, namely: Latin American and Caribbean Literature in Health Science (LILACS), International Literature in Health Sciences (MEDLINE), (PUBMED) and Allied Health Literature (CINAHL). The search was carried out in November 2020. For the selection of articles, the following inclusion criteria were considered complete articles, available electronically. 13 articles were selected that met the proposed objectives Results: it was possible to observe the predictive factors for medication adherence for the treatment of SAH in the elderly, due to the lack of information, low education, lack of family support. Final considerations: it is necessary for nurses to recognize the main factors that contribute to non-adherence to medication treatment for the elderly. Therefore, the need to create a strategy that involves embracement, health education and behavior change can favor participatory behavior that contributes to therapeutic adherence in an appropriate manner.